PLACE OF INFORMATICS IN THE NOMENCLATURE OF SCIENTIFIC SPECIALTIES - R. S. Ghiljarevsky (Informatika)
The place of informatics and other information disciplines of scientific specialties, their linkswith discussions about the nature of the phenomenon of information, as well as the trends of unification of information science and computer science in the U.S. and Europe are considered. The methods of ordering the range of specialties of reserchers in Russia are suggested.